Solar chimney power plants – Dimension matching for optimum performance. (15th August 2019) - Cottam, P.J.; Duffour, P.; Lindstrand, P.; Fromme, P.
Highlights: Thermodynamic model predicts solar chimney performance over large parameter space. Dimension matching is key to reach commercially viable power outputs. Large chimney radii up to 200 m needed to achieve power output of 900 MW. Cost model based on relative component costs identifies optimum plant dimensions. Smaller plants economically viable depending on chimney cost increase with height. Abstract: Solar chimney power plants are very large structures with the potential to generate significant amounts of electricity. Plant dimensions such as the collector diameter and chimney height and radius are important in determining system performance. The objective of this study is to identify the key parameters that drive performance. Performance was assessed in terms of power output and power output per cost. Using a detailed thermodynamic model, the plant power output was predicted for a wide range of design and operational parameters. It was found that the optimum pressure drop ratio depends on the collector and chimney radius, but not on chimney height, ambient temperature or insolation. The dimensions of the main components must be well matched to achieve best performance. Chimney radii of up to 200 m are essential to achieve maximum power generation up to 900 MW. Optimum power output exists for variation of the collector and chimney radius. However, increasing the chimney height always results in increased power generation. The physical phenomena underpinning high-performing configurations were highlighted. Power and efficiency increase with increased plant dimensions, but technological limits exist for the chimney height. A simple but robust cost model was introduced to identify optimum configurations in terms of power output per cost. Different relative costs between collector and chimney the optimum dimensions were selected. It was concluded that several smaller plants with collector radius about 3000 m are advantageous over one larger plant. Taller chimneys are economically beneficial until the specific chimney costs increase more than quadratically with height.